The Process of Occupational Sex-Typing The Feminization of Clerical Labor in Great Britain - Cohn, Samuel (Temple University Press, 2018)
Samuel Cohn's critical study of two Victorian British firms represents a radically new examination of women's work. By contrasting the Post Office, which was the first employer to use female clerks instead of males, and the Great Western Railway, one of the last employers to make this change, Cohn identifies the organizational and economic limits to female employment. The Process of Occupational Sex-Typing challenges traditional accounts of clerical feminization that invoke cultural restrictions on women's work, human capital theory, discrimination by co-workers, and the de-skilling of jobs. Further, Cohn puts forward an alternative theory of occupational sex-typing that emphasizes the high cost of male labor, differences between organizations in their ability to tolerate discrimination, the latent contradictions within internal labor markets, and competition to women from other sources of cheap labor.